Investing in children work, education, and social policy in two rich countries - Kalil, Ariel; Haskins, Ron; Chesters, Jenny (Brookings Institution Press, 2012)
"Presents new research by leading scholars in Australia and the United States on economic factors that influence children's development and the respective social policies the two nations have designed to boost human capital development"--Provided by publisher.